Assessment of Antioxidant Activities of Kenaf Leaves (Hibiscus cannabinus) Extracts - S, Ibrahim; Abdul Kadir S.A.I.A, Syed; N, Ismail; N.H, Ismail (Malaysian Journal of Science, 2005)
The antioxidant properties of petroleum ether extract [PE], dichloromethane fraction [DCM frac] and methanol crude extract [MeOH] of simple leaves of kenaf (Hibiscus cannabinus), Malvaceace family have been measured by Ferric thiocyanate (FTC) and Thiobarbituric acid (TBA) methods as described by Kikuzaki and Nakatani [1]. Other methods used for antioxidant assay are 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging and reducing power [2]. FTC and TBA method for all crude extracts at 0.02% concentration showed low absorbance values, which indicates high antioxidant activities, as compared to vitamin E and quercetin. OPPH activity of [PE] extracts and [MeOH] at both 500 Ã‚Âµ/ml, exhibited moderate activity at 50.15% and 66.93% inhibitions, respectively. However, reducing power showed low activity for all crude extracts.